High efficiency implementation of PC and PC stable algorithms yields three-dimensional graphs of information flow for the Earth' atmosphere - Deng, Yi, author; Ebert-Uphoff, Imme, author (Colorado State University. Libraries, 2014)
Causal discovery algorithms have recently been applied to several climate applications. In particular, in prior work we have developed methods to recover pathways of interaction in the global climate system, using the classic PC algorithm. However, standard implementations of the PC algorithm cannot handle the large number of variables and temporal models required for this application. This technical report shows that a more efficient implementation of the PC algorithm can provide speed gains of a factor of 1,000 or more. This in turn enables us to calculate graphs of information flow with much higher resolution grids. Furthermore, we can now - for the first time ever - calculate information flow graphs that extend over three dimensions, i.e. rather than just including one layer of the planet's atmosphere we can now capture interactions across several height layers.
September 3, 2014.
Keywords: large-scale atmospheric waves; graph of information flow; wave source; wave propagation; causal discovery; spatial; climate